If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 21 = 15 Reorder the terms: 21 + 3x = 15 Solving 21 + 3x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3x = 15 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = 15 + -21 3x = 15 + -21 Combine like terms: 15 + -21 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 8a^2+6n=18 | | 5(4c-1)-5=18c+2 | | 2x+3y=53 | | 3m^2+4m-7=0 | | 7+3=10 | | x=4+-2y | | X+((-3)x)=-8 | | 7x+17=-4 | | 2x+2=2(x-7) | | -3x-(-8)=x | | -y=8x | | -6(2r+4)=-84 | | O=4x+(-6x+7) | | -4y+4=-2(3y+7) | | 6t-4=2 | | x+2x+14=83 | | 3x+20=-1 | | f(f(t^2))=x+5 | | 28+4y-10=14y-14-2y | | -5[3+5(-3+5)]+12= | | -6(12-2w)=7(-2-3w) | | 3(2x-6)+(-6)(2x-4)= | | -64=4(-6m+2) | | 3y^2-19y+6=0 | | 20u-13+16u+33= | | -64=(-6m+2) | | 5n^2-7n-34=0 | | 3(-9)-(-13)= | | x+19+2x=-11-2x-15 | | 16x^2=764 | | 9+6(-4)= | | 6(2x-4)=3(-x+7) |